Damage identification for frame structures using vision-based measurement. (15th November 2019) - Guo, Jia; Jiao, Jian; Fujita, Kohei; Takewaki, Izuru
Highlights: A vision-based measurement framework using the camera system for damage identification is proposed, which is composed of four procedures: camera calibration, image processing, system identification and sensitivity analysis. Less number of modes is required for modal-based damage identification problems and more physical parameters could be extracted, taking advantage of the plentiful experimental data. Suitable strategies to circumvent the major drawback that the camera system suffers high levels of noise in small vibration responses at higher frequencies are developed. Abstract: Extracting physical parameters for damage identification problems from full-field measurements is a promising research because of the recent spread of vision-based measurement techniques in the experimental mechanics. This paper presents a vision-based measurement framework using the camera system for damage identification. The framework is composed of four procedures: camera calibration, image processing, system identification and sensitivity analysis. In contrast to traditional finite-point measurements, the camera system allows considerably greater non-contact measurement flexibility. Such flexibility has two important benefits: first, less number of modes is required for modal-based damage identification problems; and second, more physical parameters could be extracted, taking advantage of the plentiful experimental data. A laboratory test comparing the camera system to traditional accelerometer measurement is conducted to confirm the above advantages. Further statistic analysis shows that the major drawback of this technique is that the camera system presents high levels of noise in small vibration responses at higher frequencies. Suitable strategies to circumvent this disadvantage are developed. Moreover, a technique for practical camera calibration without the requirement that the objective plane should be strictly perpendicular to the camera axis is also demonstrated and verified by the proposed laboratory test.